Facies and Reservoir Evaluation of Mishrif Formation in Tuba Oil Field - Y. Abed Alrrawi, Dhya; A. Al-Yaseri, Abdullah; H. Seqer, Mohammed (Iraqi Journal of Science, 2023)
The Mishrif Formation is one of the most important formation in oil fields, which is located in southern part of Iraq, and it is of Upper Cretaceous age. Tuba field is located nearly 40 km SW – Basrah city. It is bounded from east by Zubair oil field (5 km distance) and from west by Rumaila (2 km distance). The Tuba oil field is situated between Zubair oil field in the east and Rumaila in the west, and is separated by two depressions.The rock (core and chips) samples have been collected systematically from cores of Mishrif Formation that are available from stores of southern oil company to prepare thin sections and slides—these slides have been examined by using microscope. These samples have been taken from all parts of the reservoir units of Mishrif, namely, mA, mB1, mB2 units. Twenty-four samples have been applied to the petrophysical tests to measure the porosity and permeability. The water and oil saturations have been identified by consulting the log documents for studied wells (7 wells). Besides, four hundred ten rockslides have been made for identifying the facies and diagenices processes.Four main facies have been diagnosed at Mishrif Formation (Grainstone, packstone, wackstone and mudstone) which are spread all over the reservoir units. Moreover, the diagentic processes have been identified by using microscope to check the rockslides, which have greatly framed the petrophysical characteristics for Mishrif Formation. These processes include dissolution, all categories of porosity, compaction, cementation, new morphisim and dolomitization.The results of the reservoir geological model show that Tuba field is an anticline fold which its extension is in (north – northwest), (south- southeast) direction. The results have proved that facies model distribution completely match the facies description in the study. This model contains Grainstone, Packstone, Wackstone and Mudstone.